The Dualistic Model of Strategic Planning - Russian Experience - Sergey O. SHOKHIN; Ekaterina V. KUDRYASHOVA (Communications of International Proceedings, 2020)
This paper aims to demonstrate the dualistic model of strategic planning with reference to Russian experience. There are two mainstreams of strategic planning. First is the social-economic strategies and the Federal law on strategic planning in Russian Federation. Second is formed by strategic presidential orders known as “may executive orders”. We try to provide the systematic view on the institutionalization of strategic planning in the dualistic model.  The model turns to be acceptable for the public management practice. However, it shows controversies and there are difficulties in implementation of the model.  Inductive and deductive reasoning combined with critical analysis are employed in this paper. The contextual approach is used in this study as well. By now the dualistic model of strategic planning was not identified. This paper will contribute greatly to the understanding of strategic management practices. The critical analysis of the strategic planning in a specific country helps to compare and improve the public governance in different countries around the world.
Keywords: Strategic Planning; Strategic Management; Public Management; Russian Federation; Legal Regulation.